HARDNESS OF WOOD IN SOME OAK SPECIES - Mladenova, Diyana; Bardarov, Nikolai (Innovation in Woodworking Industry and Engineering design, 2017)
The oaks are one of the most important species for our Dendroflora. This study of hardness complements the knowledge of the properties of their wood. Wood is a non-homogeneous material and its properties differ in different parts of the stem. Hardness is a property that is directly related to the construction of the wood. That is why knowledge of this property will be an important step towards more rational use of oak wood. The work presents data on the hardness of the wood of pedunculate oak (summer) and sessile oak (winter oak). The influence of the habitat and the radius of the stem is examined. In order to compare the individual samples, the qualitative hardness coefficient was determined.